E/CIA: Integrated information audit framework for electricity companies - Mohd Drus, Sulfeeza; Mohamed Shariff, Siti Salbiah (2008)
Information audit has become one of the key activities for large organisations in the current business environment.A study exploring the current practices of information audit in electricity companies was conducted, where two main electricity companies in Malaysia were chosen as the case companies.Empirical data showed that information audit is a new concept to these companies and hence, none of them had conducted any information audit exercise.This study proposed information audit framework, ElCIA, specifically tailored to electricity industry environment.ElCIA is hoped to help electricity companies in conducting information audit effectively.